2022
DOI: 10.1371/journal.ppat.1010631
|View full text |Cite|
|
Sign up to set email alerts
|

The structural role of SARS-CoV-2 genetic background in the emergence and success of spike mutations: The case of the spike A222V mutation

Abstract: The S:A222V point mutation, within the G clade, was characteristic of the 20E (EU1) SARS-CoV-2 variant identified in Spain in early summer 2020. This mutation has since reappeared in the Delta subvariant AY.4.2, raising questions about its specific effect on viral infection. We report combined serological, functional, structural and computational studies characterizing the impact of this mutation. Our results reveal that S:A222V promotes an increased RBD opening and slightly increases ACE2 binding as compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Further enhancement of the inhibitory effect could be due to the possibility of an allosteric effect by which compound 2 binding could prevent the adoption of the up position in the third of these RBDs. This is supported by the facts that, in the spikes in 1-up or 2-up conformations, the RBDs in up position/s interact with neighboring RBDs in the down position, while in the present 3-down structure, the contact with compound 2 prevents an optimal location of the compound-contacting subunits to stabilize the third RBD in the up position (Figure H).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Further enhancement of the inhibitory effect could be due to the possibility of an allosteric effect by which compound 2 binding could prevent the adoption of the up position in the third of these RBDs. This is supported by the facts that, in the spikes in 1-up or 2-up conformations, the RBDs in up position/s interact with neighboring RBDs in the down position, while in the present 3-down structure, the contact with compound 2 prevents an optimal location of the compound-contacting subunits to stabilize the third RBD in the up position (Figure H).…”
Section: Resultssupporting
confidence: 53%
“…The remaining 26% of the particles had the three RBDs in down positions (4.3 Å resolution; Figure D, middle and down panels). Comparison of the present dataset with our recently published datasets, which were prepared in an identical manner in the absence of any compound, showed that the 3-down class of the spike is highly enriched in the presence of compound 2 (24% of the particles versus <2% of the particles without drug). This finding is further supported by similar cryo-EM structures reported by others in which the conformation with the 3 RBDs down was represented in a small minority of the particles. , Hence, compound 2 appears to specifically induce a three RBD-down class that should inhibit binding to ACE2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D614G amino acid substitution in the S protein was one of the first changes that succeeded in being fixed in subsequent viral lineages since it increased viral transmissibility ( 5 , 6 ) (reported up-to day in >13 million genome sequences deposited in GISAID, Figure 1 ). In the summer of 2020, the B.1.177 variant spreading from Spain incorporated another mutation, A222V, in the viral S protein, a change generally considered neutral ( 7 ), although such view might be challenged by the repeated events of independent re-emergence of this mutation ( 8 ). Variants B.1.160 and B.1.258 appeared approximately simultaneously with the B.1.177 variant and coexisted with it in some countries, ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to VOIs and VOCs, minority variants also are relevant, especially in terms of virus monitorization. In fact, some of the substitutions described for less prevalent variants have later on been reported in VOCs ( 13 ), some of them via independent events of re-emergence as observed for the A222V mutation in the S protein ( 8 ).…”
Section: Introductionmentioning
confidence: 99%